Pendidikan Karakater Berbasis Terapi Muhasabah untuk Pendampingan Siswa dengan Perilaku Indisipliner di Rembang - Firdausy, Hissiyah; Fa'atin, Salmah (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2025)
Student indiscipline behavior is a challenge in the world of education that can affect the effectiveness of learning. This study aims to evaluate the effectiveness of student mentoring using muhasabah therapy in reducing indisciplinary behavior. The research method used was a quasi-experimental with a one group pretest-posttest design. The participants of this study were 28 students with indisciplinary behavior from class IX B at MTs Miftahul Huda Sarang Rembang. The intervention was carried out four times for one month using muhasabah therapy to increase students' awareness and self-reflection. The results showed a decrease in indisciplinary behavior after the implementation of muhasabah therapy (p <0.05). The average pretest score of 5.25 decreased to 3.21 in the posttest value, indicating the effectiveness of muhasbah therapy. These findings confirm that muhasabah therapy can be an alternative method in supporting character education and improving student discipline. Therefore, this approach can be recommended for application in guidance and counseling programs in schools to improve discipline.